PENGEMBANGAN MOCAF (MODIFIED CASSAVA FLOUR) UNTUK PENINGKATAN DIVERSIFIKASI PANGAN DAN EKONOMI PASCA ERUPSI MERAPI - Nugraheni, Mutiara; Handayani, Titin Hera Widi; Utama, Agung (Universitas Negeri Yogyakarta, 2015)
This activities is carried out in order to: (1) provide an alternative topost-harvest cassava in farmer groups of Mekar Sari Lor, Karang Gawang,Jumoyo, Cangkringan, Magelang regency which able to produce food based onmocaf that can be accepted by consumers, (2) provide an alternative toconsumers in food based on mocaf that ready to use and have a long shelf life,and (3) home industry development opportunities in Karang Gawang in anattempt to economic recovery after eruption of Merapi The steps taken to achieve the goal of this activities is to provide atheory characteristic of mushroom and way of processing, sanitation, hygieneand food sertification, packaging and selling price determination and long shelflife; practice make flour mocaf and products based on mocaf, namely egg roll,sempe,kembang goyang, and pangsit. Preference test for the products, the calculationofthesaleprice;acceptancetestingforproductsandpricesattheconsumerlevelanddeterminationofshelflifeasoneofthedatathatwillappearinthepackaging.Alternative processing of cassava into mocaf flour be implemented. Theyield of mocaf flour from cassava is 35% with a production cost of Rp 3300.00.The sale price with 40% mark-up is Rp 5000.00. Diversification processedproduct based on mocaf flour are egg roll, sempe, kembang goyang and pangsitwhich have a shelf life of 3 months. This products have opportunities to behome industry development because have a competitive price; mocaf flour Rp5,000.00/kg, egg roll Rp 6000.00/100 grams, pangsit Rp5000.00/200 grams,sempe Rp 5000.00/100 grams, and kembang goyang Rp 5000.00/100 grams